2022
DOI: 10.1038/s41598-022-26189-9
|View full text |Cite
|
Sign up to set email alerts
|

Intense chorus waves are the cause of flux-limiting in the heart of the outer radiation belt

Abstract: Chorus waves play a key role in outer Van Allen electron belt dynamics through cyclotron resonance. Here, we use Van Allen Probes data to reveal a new and distinct population of intense chorus waves excited in the heart of the radiation belt during the main phase of geomagnetic storms. The power of the waves is typically ~ 2–3 orders of magnitude greater than pre-storm levels, and are generated when fluxes of ~ 10–100 keV electrons approach or exceed the Kennel–Petschek limit. These intense chorus waves rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 68 publications
5
22
0
Order By: Relevance
“…The electron fluxes exceed the K-P limit predominantly on the dawn side. The dawn MLT region is also associated with the highest intensity precipitation reported here, as well as with the highest chorus wave activity as reported in many earlier studies (e.g., Aryan et al, 2022;Chakraborty et al, 2022;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The electron fluxes exceed the K-P limit predominantly on the dawn side. The dawn MLT region is also associated with the highest intensity precipitation reported here, as well as with the highest chorus wave activity as reported in many earlier studies (e.g., Aryan et al, 2022;Chakraborty et al, 2022;Chen et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Chakraborty et al. (2022) also showed that the K‐P limiting processes are associated with the generation of a separate population of very intense chorus waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong substorms with Kp ∼ 5-6 and AE ∼ 600-1,000 nT usually correspond to a time-and MLT-averaged chorus wave power 𝐴𝐴 ⟨𝐵𝐵 2 𝑤𝑤 ⟩𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡𝑡 ∼ (50) 2 pT 2 at latitudes λ ∼ 15° of cyclotron resonance with 100 keV electrons near the loss-cone at L ∼ 5-6 (Agapitov et al, 2018). To reduce the lifetime τ L to its minimum value, τ SD (E min ) ∼ 140 s, the average wave power must increase up to 𝐴𝐴 ⟨𝐵𝐵 2 𝑤𝑤 ⟩𝑡𝑡 ∼ (280) 2 pT 2 , a level sometimes observed for hours at L ∼ 5 during geomagnetic storms and substorms (Chakraborty et al, 2022;Elliott et al, 2022;C. Tang et al, 2023), or during microbursts (Zhang et al, 2022).…”
Section: Extremely Strong Electron Injectionsmentioning
confidence: 99%
“…Strong substorms with Kp ∼ 5–6 and AE ∼ 600–1,000 nT usually correspond to a time‐ and MLT‐averaged chorus wave power false〈Bw2false〉t,MLTfalse(50false)2 ${\langle {B}_{w}^{2}\rangle }_{t,MLT}\sim {(50)}^{2}$ pT 2 at latitudes λ ∼ 15° of cyclotron resonance with 100 keV electrons near the loss‐cone at L ∼ 5–6 (Agapitov et al., 2018). To reduce the lifetime τ L to its minimum value, τ SD ( E min ) ∼ 140 s, the average wave power must increase up to false〈Bw2false〉tfalse(280false)2 ${\langle {B}_{w}^{2}\rangle }_{t}\sim {(280)}^{2}$ pT 2 , a level sometimes observed for hours at L ∼ 5 during geomagnetic storms and substorms (Chakraborty et al., 2022; Elliott et al., 2022; C. Tang et al., 2023), or during microbursts (Zhang et al., 2022). Such large amplitudes can lead to electron trapping and nonlinear acceleration (Katoh & Omura, 2007; Vainchtein et al., 2018; Zhang et al., 2019), but significant wave amplitude modulations and random phase jumps between and inside intense wave packets usually restore a diffusive‐like electron transport that can be approximated by quasi‐linear diffusion (Artemyev et al., 2021, 2022; Z.…”
Section: Upper Flux Limits Based On Dynamical Equilibrium With Electr...mentioning
confidence: 99%